Inclusive Research: Making a Difference to Policy and Legislation. Issue 1 (21st November 2013) - Johnson, Kelley; Minogue, Gerard; Hopklins, Rob
<x xml:space="preserve">Abstract</x> Background While inclusive research has become an important stream in research with people with intellectual disabilities, there is a tension between the possibly empowering research process and the strength of the research itself to make social change happen. In this paper, we explore the contribution of two inclusive qualitative research studies in Australia and the Republic of Ireland to change in policy and legislation. Materials and methods Both studies used qualitative methods including life stories and focus groups to explore the issue of sexuality and relationships. In both studies, people with intellectual disabilities were actively involved in undertaking the research. Results Both studies revealed that it was difficult for people with intellectual disabilities to express their sexuality openly or to form adult relationships. Conclusions Both studies were used by people with intellectual disabilities and their supporters to promote change in which they had a heard voice. Accessible Abstract This paper is about how people with intellectual disabilities and their supporters can use research which they have done to change policies and laws that affect them. When people with intellectual disabilities are doing research it is called inclusive research.We write about two research studies which were about the sexual lives and relationships of people with intellectual disabilities. One research study was in Australia and one was in the Republic of Ireland.In the Australian study, Living Safer Sexual Lives, 25 people with intellectual disabilities told their life stories and talked about sexuality and relationships.In the Irish study people with intellectual disabilities told life stories and talked with other people with intellectual disabilities about their sexuality and relationships in groups. These are called focus groups.In this paper we explore 4 questions that arose from these studies. Question 1. What impact does doing research have on the people who are involved in it? People with intellectual disabilities in Australia were members of the group that guided the research. They were partners in its design, in deciding what questions should be asked about sexuality and relationships., and thinking about what was found out. They became involved in making films about the study. They learned a lot about research, sexuality and relationships and became members of a government committee to change policy about sexuality and people with disabilities. In Ireland people with intellectual disabilities involved in doing the research talked together about their lives. They then talked with 16 groups of people with intellectual disabilities about their relationships and sexuality. They learned about research and about sexuality and developed plays about their experiences. Question 2. To what extent can inclusive research change policy and practice? In Australia the research led to a change in government policy about sexuality and people with disabilities. The new policy clearly stated people with disabilities had rights to relationships and to a sexual life. It set out rights and responsibilities for people with intellectual disabilities and service providers about relationships and sexuality. It took a long time to get a change in policy and people with intellectual disabilities were part of the getting the change to happen. In Ireland there is a law which says that it is illegal to have some forms of sex with people with intellectual disabilities. From the research people with intellectual disabilities became involved in talking with government about changing this law so that it gives them more rights to a sexual life. The law has not changed yet but the voices of people with intellectual disabilities are now being heard. Question 3 When does research shift into being advocacy? How does this happen? People with intellectual disabilities in both studies became advocates to get change to happen. Partly this was because they had become more 'expert' about sexuality and relationships and the policy and law. They were angry at what they had found out in the research and wanted to get change to happen. Question 4 What added value does including people with intellectual disabilities as researchers give to the research? People with intellectual disabilities had knowledge and experience that made it possible for the research in both Australia and Ireland to happen. They were important in how the research was done and what was done with it after it was finished.